THE PEACE NARRATIVE AND INTERFAITH NOTIONS OF SEKAR AYU COMMUNITY - Mibtadin Mibtadin (Analisa: Journal of Social Science and Religion, 2022)
The presence of Islamist activism in Ngargoyoso encourages the role of places of worship from places of voice of harmony to mouthpieces of intolerance. Sekar Ayu's interfaith women community counters the intolerant narrative. How did Sekar Ayu proclaim peace in Ngargoyoso? The purpose of this study is to determine the role of Sekar Ayu in building peace in Ngargoyoso. This research is a descriptive qualitative research with a sociology of religion approach. Data collection was through direct observation, in-depth interviews, and documentation. Its data analysis uses interactive analysis models including data reduction, data delivery, and conclusions. Sekar Ayu's interfaith women community as a social movement of Ngargoyoso civil society is actively developing a culture of peace. First, Sekar Ayu actively builds communication and dialogue between religious groups and advocates for humanitarian and religious issues at the lower community level based on places of worship. Second, Sekar Ayu became a space for interfaith community encounters with various activities such as places of worship and family gatherings in it with discussions about religious, social, and cultural issues as a form of life dialogue. Third, Sekar Ayu empowers interfaith women to build a mutually beneficial life between religious groups. Fourth, Sekar Ayu's activities are expected to be a dialogue of sustainable life by emphasizing an inclusive, pluralist perspective, by promoting religion as a social ethic.